“La Tribuna”. Una novela a caballo entre dos mundos - Durán Vázquez, José Francisco (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The present article tries to analyze the work "The Platform" of Emilia Pardo Bazán, giving special attention to the labour reality that is described in the novel, reality that, as we believe, places in a moment of transition between a society preindustrial and different in process of industrialization. It is, from this point of view, a document of the first order, on having treated itself about the first novel that in Spain there describes the working world with the zeal documentary maker who characterized to the naturalistic movement. From this perspective the work has an important historical and sociological interest. It is precisely the latter dimension the one that tries to explore this article, analyzing the working environment that is described in the novel as a very illustrative example of the social and cultural transformations that gave place to the birth of the industrial society. The article begins with a few small biographical notes of the authoress; later one will refer to the novel in the context of the naturalistic movement to which it(he,she) belongs(concerns); later one will allude to the political events that use as frame to the novel and that allow to understand many of the reactions that before they demonstrate the principal prominent figures; finally we will enter the analysis of the labour reality that is described in the work, central topic of the writing that later we present.